2012
DOI: 10.1016/j.schres.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Auditory steady state response in the schizophrenia, first-degree relatives, and schizotypal personality disorder

Abstract: The power and phase synchronization of the auditory steady state response (ASSR) at 40 Hz stimulation are usually reduced in schizophrenia (SZ). The sensitivity of the 40 Hz ASSR to schizophrenia spectrum phenotypes, such as schizotypal personality disorder (SPD), or to familial risk has been less well characterized. We compared the ASSR of patients with SZ, persons with schizotypal personality disorder, first degree relatives of patients with SZ, and healthy control participants. ASSRs were obtained to 20, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 50 publications
3
76
0
Order By: Relevance
“…2012, Nakao & Nakazawa 2014). Interestingly, also in this testing paradigm, the response amplitude of single cells, in terms of relative change in mean firing rate, showed a significant decrease in Df(h15q13)/+ compared to wild‐type mice (Krishnan et al .…”
Section: Resultsmentioning
confidence: 99%
“…2012, Nakao & Nakazawa 2014). Interestingly, also in this testing paradigm, the response amplitude of single cells, in terms of relative change in mean firing rate, showed a significant decrease in Df(h15q13)/+ compared to wild‐type mice (Krishnan et al .…”
Section: Resultsmentioning
confidence: 99%
“…Following the original and landmark observation that 40 Hz ASSR is specifically deficient in schizophrenia subjects (Kwon et al, 1999), numerous reports have broadly confirmed the finding (Brenner et al, 2003;Krishnan et al, 2009;Light et al, 2006;Spencer, 2011;Spencer et al, 2008;Vierling-Claassen et al, 2008), and extended it to first-degree relatives of schizophrenia subjects (Hong et al, 2004;Rass et al, 2012), suggesting that such a deficit may be a trait marker. However, it is pertinent to note that 40 Hz ASSR deficit is not specific to schizophrenia and extends to some neuropsychiatric conditions including bipolar disorder (Oda et al, 2012;Rass et al, 2010) and autism spectrum disorders (Rojas et al, 2011;Wilson et al, 2007).…”
Section: Introductionmentioning
confidence: 89%
“…Generally, the ASSR phase locking factor (PLF) has been found to be superior in sensitivity to a Fourier power analysis in analyzing the ASSR – the PLF measures the consistency of time-locked responses to each individual stimulus in the ASSR and is reduced in schizophrenia. Importantly, the ASSR abnormality in schizophrenia appears not to be an artifact of medication [14] and is reduced in unaffected and psychotropic medication naïve 1st degree relatives of schizophrenia patients [15]. Psychotic bipolar patients also show GBO deficits but do not show the schizophrenia-specific lateralized pattern of greater deficits in the left hemisphere, where numerous MRI studies show a similarly left-lateralized reduction of cortical gray matter [14].…”
Section: Importance Of γ Band Oscillation Activity In Brain Circuit Cmentioning
confidence: 99%